Fully automated structural MRI of the brain in clinical dementia workup. (June 2017) - Persson, Karin; Selbæk, Geir; Brækhus, Anne; Beyer, Mona; Barca, Maria; Engedal, Knut
Background: The dementia syndrome has been regarded a clinical diagnosis but the focus on supplemental biomarkers is increasing. An automatic magnetic resonance imaging (MRI) volumetry method, NeuroQuant® (NQ), has been developed for use in clinical settings. Purpose: To evaluate the clinical usefulness of NQ in distinguishing Alzheimer's disease dementia (AD) from non-dementia and non-AD dementia. Material and Methods: NQ was performed in 275 patients diagnosed according to the criteria of ICD-10 for AD, vascular dementia and Parkinson's disease dementia (PDD); the Winblad criteria for mild cognitive impairment; the Lund-Manchester criteria for frontotemporal dementia; and the revised consensus criteria for Lewy body dementia (LBD). Receiver operating curve (ROC) analyses with calculation of area under the curve (AUC) and regression analyses were carried out. Results: Forebrain parenchyma (AUC 0.82), hippocampus (AUC 0.80), and inferior lateral ventricles (AUC 0.78) yielded the highest AUCs for AD/non-dementia discrimination. Only hippocampus (AUC 0.62) and cerebellum (AUC 0.67) separated AD from non-AD dementia. Cerebellum separated AD from PDD-LBD (AUC 0.83). Separate multiple regression analyses adjusted for age and gender, showed that memory (CERAD 10-word delayed recall) (beta 0.502, P  < 0.001) was more strongly associated to the hippocampus volume than the diagnostic distinction of AD versus non-dementia (beta −0.392, P  < 0.001). Conclusion: NQ measures could separate AD from non-dementia fairly well but generally poorer from non-AD dementia. Degree of memory impairment, age, and gender, but not diagnostic distinction, were associated to the hippocampus volume in adjusted analyses. Surprisingly, cerebellum was found relevant in separating AD from PDD-LBD.